Customer Relationship Management in Retail Sector: The Mula Mantra for Success - C, Sumith (Journal of Commerce and Trade, 2007)
Increasing number of retail business customer relationship management is a basis for achieving efficiency and leverage competitive advantage. The era changes the approach of the producer to the customer oriented approach. Today the customer drives the organization because the freedom of choice and availability of information that the customer can access at every time. Customer Relationship Management pays vital role in the organization to identify the needs and wants of the customer. Customer Relationship Management aims is to retain the prospective customer in the brand and make them loyal to the product. Customer Relationship Management tools helps the organization to identify and implementing the strategies to retain the customer.